The Phantom Urine: An Unexpected Finding during a Routine Cesarean Section - Maria Pagnozza; Chahin Achtari; Jean-Yves Meuwly; David Baud (Case Reports in Obstetrics and Gynecology)
We present here an atypical finding during an elective repeat cesarean section. Despite urine flow through an indwelling bladder catheter, bladder remains distended during the whole procedure. Unexpected anatomical variations and malformations can make routine surgery challenging. Urinary tract anomalies should be suspected in cases of unexpected difficult bladder catheterization.